Influence of Combined Mechanical Processes on Tribological Properties of Tool Steels Vanadis 8 and Vancron 40 With a Similar Hardness - Toboła, Daniel; Łętocha, Aneta (Frontiers in Mechanical Engineering, 2021)
Surface integrity is important factor for components exposed to wear, like cold working tools, which need to possess high hardness combined with high wear resistance. Surface treatments such as grinding, hard turning, and hard turning with slide burnishing have been developed for its improvement. Vancron 40 and Vanadis 8 tool steels, of different chemical composition and different types and amounts of carbides, were now investigated. Heat treatment was carried out in vacuum furnaces with gas quenching to hardness of Vancron 64 ± 1 HRC and of Vanadis 65 ± 1 HRC. 3D topography, optical and scanning electron microscopy, X-ray diffraction and ball-on-disc tribological tests against Al2O3 and 100Cr6 balls as counterparts were used to examine wear and friction. For both steels, the lowest values of dynamic frictions and wear rates against Al2O3 counterbodies were achieved after sequential process of hard turning with slide burnishing with a burnishing force of 180 N. For alumina balls, the increase of wear resistance, achieved after hard turning plus burnishing in comparison to grinding exceeds 50 and 60%, respectively for Vanadis 8 and Vancron 40 steels.